2017
DOI: 10.1101/203943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Degeneracy in hippocampal physiology and plasticity

Abstract: Degeneracy, defined as the ability of structurally disparate elements to perform analogous function, has largely been assessed from the perspective of maintaining robustness of physiology or plasticity. How does the framework of degeneracy assimilate into an encoding system where the ability to change is an essential ingredient for storing new incoming information? Could degeneracy maintain the balance between the apparently contradictory goals of the need to change for encoding and the need to resist change t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 594 publications
(1,032 reference statements)
0
46
0
Order By: Relevance
“…This demonstration was constrained biophysically by the ion channel gating and kinetic properties and physiologically validated by STA and excitability measurements, all of which were obtained from hippocampal pyramidal neurons. Our results suggest that hippocampal neurons have significant degrees of freedom to achieve the specific encoding and homeostasis targets without cross-interferences in these processes 8 . Although our conclusions could potentially extend to other neuronal subtypes, such extrapolations should specifically account for biophysical characteristics of ion channels expressed in those neurons and the STA and excitability measurements from there as well.…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…This demonstration was constrained biophysically by the ion channel gating and kinetic properties and physiologically validated by STA and excitability measurements, all of which were obtained from hippocampal pyramidal neurons. Our results suggest that hippocampal neurons have significant degrees of freedom to achieve the specific encoding and homeostasis targets without cross-interferences in these processes 8 . Although our conclusions could potentially extend to other neuronal subtypes, such extrapolations should specifically account for biophysical characteristics of ion channels expressed in those neurons and the STA and excitability measurements from there as well.…”
mentioning
confidence: 77%
“…This error signal is then employed by the system to organize its parametric space to achieve a given function, with the specific structural components chosen to achieve the function determined by the internal state of the system, neuromodulatory tones and the nature of afferent signals. A specific instance of such a broad description is with reference to the role of calcium homeostasis in maintaining channel densities through calcium-dependent transcription that is dependent on a calcium error signal 7,8,10,15,44 . Here, it has been shown that the solutions achieved by neurons and their networks could recruit disparate channels and receptors depending on the specific components of the network and the nature of afferent signals 15,44 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations